The Importance of Alternative Solar Energy Sources and the Advantages and Disadvantages of Using Solar Panels in This Process - Abdikarimov Fakhriddin; Tulakov Jakhongir (Research Parks Publishing LLC, 2019)
This article reviews and analyzes the advantages and disadvantages of alternative solar energy and the use of solar panels in this process. The solar energy that is falling on the photoelements under a certain angle depends on environmental climax, season, and location. Atmospheric changes also lead to changes in the transverse and direct rays of light, which does not change the light, spectrum and intensity of falling light. These changes will change the principle of operation of the QES. Also, suggestions and recommendations regarding the risks of using solar panels are provided. Moto electric devices work full time in the morning and in the evening at low power. But the highest power supply is late at night. In addition, the energy generated dramatically changes rapidly due to weather changes. In order to eliminate these shortcomings, the AES uses electric accumulators, or it can be used to transfer energy to other types of energy, and it is also used for hydraulic accumulator stations or hydrogen power. At present, the problem is solved by building a common energy system.